Has the world changed? My neighbor might know effects of social context on routine deviation - Tilmann Betsch; Stefanie Lindow; Christoph Engel; Corina Ulshöfer; Janet Kleber (Max Planck Institute for Research on Collective Goods, 2011)
In two experiments we studied the effects of behavioral models on routine deviation decisions in observers. Participants repeatedly chose among four card-deck lotteries together with a human model (confederate, Exp. 1) or a non-human model (computer, Exp. 2) that made correct decisions in the majority of the trials. In a learning phase, participants acquired a choice routine (preferring one deck over others). In a subsequent test phase, participants had to adapt to changes in the payoff structure that required them to deviate from their routine. We found a strong tendency to maintain the routine despite negative feedback (routine effect). In a social situation (Exp.1), models decrease routine effects more intensely than in non social situations (Exp.2). The process of adaptation follows a belief updating process. Results indicate that the model effect is not due to an increase of the sample of relevant information nor to application of a simply copy heuristic. Rather, deviation models may provide a cue for change that fosters reevaluation of the situation in the observer.
Keywords: 330; experienced-based decision making; routine; habit; adaptation; social influence; Bayesian updating; novelty; Entscheidung; Verhaltensökonomik; Anpassung; Soziale Beziehungen; Test